Effects of Bischofite Gel on Reparative Processes in Wound Healing - Soldatov, Vladislav O. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: The currently available information on the bischofite mineral pharmacodynamics suggests that gels based on it have wound-healing properties. It was shown that bischofite has anti-inflammatory, immunomodulatory, and reparative activity. Materials and Methods: Experiments were performed on 36 male rats. Using a blade, a linear wound length of 50 mm was modeled. Animals were divided into four groups: (1) Control; (2) Bischofite (500 mg of gel with bischofite per wound area for 7 days); (3) Actovegin (500 mg of Actovegin gel on the wound area for 7 days); and (4) Contractubex (500 mg of Contractubex gel for 7 days wound area). About the wound healing effect of the drugs was judged by studying the physicomechanical properties, determining the concentration of hydroxyproline (HP), and calculating the ratio of collagen 1 and 3 types. Results: The greatest strength of the wound defect, significantly greater than in the control (P < 0.01), was obtained in the group that received the bischofite gel (13.70 ± 0.76 N). Actovegin also demonstrated a positive reparative effect (12.60 ± 0.63 N, P < 0.05), significantly lower (P < 0.01) than in the control strength was obtained in the group using Contractubex (9.65 ± 0.59 N). In the calorimetric analysis, it was found that the highest concentration of HP was contained in the tissues of wound defects in animals treated with Contractubex; however, there was no statistically significant difference with the control group, significantly lower in comparison with the control (P < 0.05) concentration of selenium, contained tissues of simulated wounds in animals treated with bischofite gel (79.7% of the control). When assessing the ratio of collagens I and III in the tissues of the wound defect when dyeing with picrosirius red, it was found that, by the number of mature collagen fibers, the studied groups can be arranged in the following sequence (descending): Bischofite > Actovegin > Control > Contractubex. Conclusions: The study showed that the best results were obtained with external use of the gel with bischofite. Actovegin has a less significant but pronounced reparative effect on this model. The least satisfactory results were obtained when applying Contractubex.